Analysis of Information Search Behaviour Based on The Age of Indonesian Outbound Traveler - Batari Toja, Tenri Muthia; K. Kausar, Devi Roza; Puspita, Nungky; Yuan, Yulan (Stupa, 2021)
This study aims to determine trends in choosing information channels and conducting overseas travel activities with a focus on "Analysis of Information Search Behaviour based on the age of Indonesian Overseas Tourist”. The factors tested in this study are information source search behavior that influences the choice and ease of access chosen as Univariate Variables with classification based on the age of Indonesian tourists planning to go abroad. The research design used is a quantitative approach. The population in this study is the Indonesian population who will plan an overseas trip represented by 200 samples. The technique is nonprobability sampling with non-probability sampling methods, through purposive sampling. The analytical method used is the analysis of the use of Pie chart and the F test (anova analysis). The results showed that there were no differences in the average information source search behavior that influenced the choice and ease of access chosen based on the age characteristics of Indonesian overseas tourist. Personal sources are chosen as sources of information that influence choices because interpersonal communication is the most effective type of communication to change attitudes and opinions. The travel agency was chosen for the ease of access because it provides tangible services to tourists.